Diversity and inclusion in Brazilian audit firms? Always changing to remain the same - Ribeiro, Douglas Tadeu de Oliveira (2023)
In this study, we investigated the persisting lack of diversity and inclusion in auditing firms, despite the existence of programs announced by major Brazilian auditing firms, utilising Bourdieus social theory. We applied his theoretical foundation to understand how the institutional environment can perpetuate and reinforce power domination by a hegemonic group through symbolic violence against other marginalised groups, minority majorities. Considering that Bourdieus theory extends the analysis to agency and structure, we used an intersectional approach to interpret how these power structures exert influence and affect people differently, depending on each individuals subjectivity, according to the methodology proposed by Lelia Gonzalez (1984). The work consists of two parts that compose the discussion and complement each other under different dimensions: (i) in-depth interviews from the perspective of the interviewed individuals (individual dimension) and from the perspective of the group (organisational/institutional level); and (ii) autoethnography from the dual perspective of auditor and researcher, seeking to situate himself within and outside the research field to understand and discuss the structure of auditing firms. The findings indicate that the minorities act individually to keep their places in audit firms and the racism still persists despite their discourse of diversity. This dissertation represents a significant departure from traditional narratives within the accounting literature, offering a counter-hegemonic and subversive perspective by virtue of its authorshipa black Brazilian auditor and researcher exploring the experiences of black audit professionals. Drawing inspiration from Conceição Evaristos concept of escrevivência, this study transcends individual life stories to resonate with the collective struggle of black individuals in the white-dominated audit profession in Brazil. Unlike previous studies, which often viewed diversity through a singular lens shaped by patriarchy and gender differences, this research adopts an intersectional approach. It not only highlights the inadequacy of current initiatives, such as extended maternity leave, in addressing the nuanced needs of minoritised groups but also delves into the complexities arising from the juxtaposition of multiple identities considering mainly the social markers of race, gender and class. By illuminating the unique challenges faced by individuals belonging to various marginalised groups simultaneously, this study emphasises the imperative of recognizing and addressing these intersections to ensure genuine equity in professional spaces. Moreover, this research introduces the groundbreaking concept of intersectional habitus, revealing how black auditors navigate the existing and well established norms of the audit profession. They transcend individual efforts, forming supportive networks reminiscent of quilombos during the Brazilian slavery period. This innovative approach sheds light on the collective resilience of black professionals, paving the way for a more inclusive future within large audit firms and prompting critical engagement among current and future black professionals. Future studies may be devoted to understanding how other groups are minorized and their practices of resistance. The practical implications of this research are the need to adopt affirmative actions by audit firms to reduce or eliminate the obstacles faced by minoritised groups.